Space, place, and literary representations of the landscapes of California, 1880-1917 - Sikand-Youngs, Nathaniel Rajinder (2020)
Space and place are foundational concepts in geography and the humanities more broadly, but usable, concrete definitions for them have yet to be pinned down. This dissertation begins by offering one such approach, where a place is the material result of the convergence of myriad spatial factors upon a particular geographical and temporal location, and space is the immaterial effect that a place becomes when it exceeds its locationality to affect another remote location and in so doing ceases to be a place. I then put these ideas to work by analysing the landscapes of three Californian novels: Jack London’s The Valley of the Moon (1913), Frank Norris’s The Octopus (1901, set in the early 1880s), and Mary Hunter Austin’s The Ford (1917). My dissertation argues that each novel adopts a distinct method of constructing geography, which enables them to articulate their respective politics – individualist white supremacy, naturalistic anti-corporatism, pro-industrial environmentalism – and to express their conceptions of the different Californian landscapes in which they are set.